The Orphanage : a novel - Z͡Hadan, Serhiĭ, 1974- (Margellos world republic of letters book., 2021)
"When hostile soldiers invade a neighboring city, Pasha, a thirty-five-year-old Ukrainian language teacher, sets out for the orphanage where his nephew Sasha lives, now in occupied territory. Venturing into combat zones, traversing shifting borders, and forging uneasy alliances along the way, Pasha realizes where his true loyalties lie in an increasingly desperate fight to rescue Sasha and bring him home."--Publisher.